Мethods experimental research working characteristics of the electromagnetic shock absorber - Rozhkova, S.; Rozhkov, S.; Рожкова, С. Э.; Рожков, С. П; Рожкова, С. Е. (Харківський національний автомобільно-дорожній університет, 2015)
Description of the technique of experimental research and building of the working characteristics of the electromagnetic shock absorber based on the properties of the cylindrical linear machine. A mathematical model that describes the experimental study was built. The design of the experimental plant and the principle of experimental measurements was described.
Методика экспериментальных исследований рабочих характеристик электромагнитного амортизатора
Методика експериментальних досліджень робочих характеристик електромагнітного амортизатора
Keywords: Electromagnetic shock absorber; cylindrical linear machine; experimental plant; electromotive force; Ampere force; Электромагнитный амортизатор; цилиндрическая линейная машина; экспериментальный стенд; электродвижущая сила; сила Ампера; Електромагнітний амортизатор; циліндрична лінійна машина; експериментальний стенд; електрорушійна сила; 629.3.027.3